A Multi‐Family Group Intervention for Adolescent Depression: The BEST MOOD Program. Issue 2 (9th May 2016) - Poole, Lucinda A.; Lewis, Andrew J.; Toumbourou, John W.; Knight, Tess; Bertino, Melanie D.; Pryor, Reima
Abstract : Depression is the most common mental disorder for young people, and it is associated with educational underachievement, self‐harm, and suicidality. Current psychological therapies for adolescent depression are usually focused only on individual‐level change and often neglect family or contextual influences. The efficacy of interventions may be enhanced with a broader therapeutic focus on family factors such as communication, conflict, support, and cohesion. This article describes a structured multi‐family group approach to the treatment of adolescent depression: Behaviour Exchange Systems Therapy for adolescent depression (BEST MOOD). BEST MOOD is a manualized intervention that is designed to address both individual and family factors in the treatment of adolescent depression. BEST MOOD adopts a family systems approach that also incorporates psychoeducation and elements of attachment theories. The program consists of eight multifamily group therapy sessions delivered over 2 hours per week, where parents attend the first four sessions and young people and siblings join from week 5. The program design is specifically aimed to engage youth who are initially resistant to treatment and to optimize youth and family mental health outcomes. This article presents an overview of the theoretical model, session content, and evaluations to date, and provides a case study to illustrate the approach.